Helicobacter pylori infection and serum magnesium in kidney disease; current concepts - Banafsheh Yalameha; Parto Nasri (Society of Diabetic Nephropathy Prevention, 2020)
One of the problems of renal disease patients, especially patients undergoing dialysis, is gastrointestinal complications caused by Helicobacter pylori infection. H. pylori has still high prevalence in most populations. It is estimated that about half of the world population is infected with this infection and it can change levels of most micronutrients such as magnesium. Different studies demonstrate that H. pylori may affect the metabolism of magnesium in renal failure. The present paper investigated the association of serum magnesium level with H. pylori infection. Nevertheless, it should be more evaluated by researchers and still many studies are necessary to confirm this issue.